The MicroRNA Landscape of MYCN-Amplified Neuroblastoma - Misiak, Danny; Hagemann, Sven; Bell, Jessica L.; Busch, Bianca; Lederer, Marcell; Bley, Nadine; Schulte, Johannes H.; Hüttelmaier, Stefan (Frontiers in Oncology, 2021)
MYCN gene amplification and upregulated expression are major hallmarks in the progression of high-risk neuroblastoma. MYCN expression and function in modulating gene synthesis in neuroblastoma is controlled at virtually every level, including poorly understood regulation at the post-transcriptional level. MYCN modulates the expression of various microRNAs including the miR-17~92 cluster. MYCN mRNA expression itself is subjected to the control by miRNAs, most prominently the miR-17~92 cluster that balances MYCN expression by feed-back regulation. This homeostasis seems disturbed in neuroblastoma where MYCN upregulation coincides with severely increased expression of the miR-17~92 cluster. In the presented study, we applied high-throughput next generation sequencing to unravel the miRNome in a cohort of 97 neuroblastomas, representing all clinical stages. Aiming to reveal the MYCN-dependent miRNome, we evaluate miRNA expression in MYCN-amplified as well as none amplified tumor samples. In correlation with survival data analysis of differentially expressed miRNAs, we present various putative oncogenic as well as tumor suppressive miRNAs in neuroblastoma. Using microRNA trapping by RNA affinity purification, we provide a comprehensive view of MYCN-regulatory miRNAs in neuroblastoma-derived cells, confirming a pivotal role of the miR-17~92 cluster and moderate association by the let7 miRNA family. Attempting to decipher how MYCN expression escapes elevated expression of inhibitory miRNAs, we present evidence that RNA-binding proteins like the IGF2 mRNA binding protein 1 reduce miRNA-directed downregulation of MYCN in neuroblastoma. Our findings emphasize the potency of post-transcriptional regulation of MYCN in neuroblastoma and unravel new avenues to pursue inhibition of this potent oncogene.